Kendali Cerdas Kelistrikan Rumah menggunakan Node-Red Berbasis Raspberry Pi-3 B+ : Home Electrical Intelligent Control using Node-Red Based on Raspberry Pi-3 B + - Hidayat, Bayu (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2021)
In this era, technological growth is so rapid in various fields, one of which is gadget and internet. Lately, the use of gadgets and the internet has functioned as a home control and monitor system, or we usually call it smart home. Lots of technology development in the field of smart home, this is for the sake of convenience and comfort in homework. Therefore humans need a system that can control the lights of the house remotely by using internet networks. Sometimes we as humans forget to turn off the lights when out of the house, with the remote home light controller using the internet network we can turn off the lights of the house without having to go back home. The equipment used is utilizing a Raspberry Pi mini computer, relay module and AC light dimmer module. The Raspberry Pi functions as a microcontroller that drives the relay module as a switch and the module dimmer AC light as a regulator of the brightness of the light. For home light control using a web that can be accessed through a browser on laptops, computers and smartphones. And web creation utilizes the Node-RED application. The results achieved in this mini project are to produce a system that can control the house electrical remotely with internet networks and utilize Raspberry Pi-based Node-RED applications..